Alzheimer's Disease: The Role of Microglia in Brain Homeostasis and Proteopathy - Clayton, Kevin A.; Van Enoo, Alicia A.; Ikezu, Tsuneya (Frontiers in Neuroscience, 2017)
Brain aging is central to late-onset Alzheimer’s disease (LOAD), although the mechanisms by which it occurs at protein or cellular levels are not fully understood. Alzheimer’s disease is the most common proteopathy and is characterized by two unique pathologies: senile plaques and neurofibrillary tangles, the former accumulating earlier than the latter. Aging alters the proteostasis of amyloid- peptides and microtubule-associated protein tau, which are regulated in both autonomous and non-autonomous manners. Microglia, the resident phagocytes of the central nervous system, play a major role in the non-autonomous clearance of protein aggregates, whose function is significantly altered by aging and neurodegeneration. This is genetically supported by the association of microglia-specific genes, TREM2 and CD33, and late onset Alzheimer’s disease. Here, we propose that the functional characterization of microglia, and their contribution to proteopathy, will lead to a new therapeutic direction in Alzheimer’s disease research.